2022
DOI: 10.1002/jpen.2317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of infusion frequency on quality of life in patients receiving home parenteral nutrition

Abstract: Home parenteral nutrition (HPN) may be needed as a long-term therapy for patients with chronic intestinal failure whose clinical condition does not allow complete weaning of the parenteral nutrition (PN) solution. HPN is a time-consuming and clinically complex therapy and can negatively affect quality of life (QOL). The level of dependency on HPN, specifically, infusion frequency, has been proposed as a factor that may have an effect on QOL in patients receiving HPN. The primary aim of this qualitative review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(262 reference statements)
0
5
0
Order By: Relevance
“…Clearly these two factors are connected, as demonstrated recently by Samuel et al that <5 HPN infusions/week was significantly associated with returning to work after HPN commencement 34 . A recent qualitative review also concluded that improvement in quality of life is associated with a reduction in HPN frequency and that the frequency reduction is highly prioritized among HPN‐dependent patients 37 …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Clearly these two factors are connected, as demonstrated recently by Samuel et al that <5 HPN infusions/week was significantly associated with returning to work after HPN commencement 34 . A recent qualitative review also concluded that improvement in quality of life is associated with a reduction in HPN frequency and that the frequency reduction is highly prioritized among HPN‐dependent patients 37 …”
Section: Discussionmentioning
confidence: 85%
“…34 A recent qualitative review also concluded that improvement in quality of life is associated with a reduction in HPN frequency and that the frequency reduction is highly prioritized among HPN-dependent patients. 37 Further work is now required to evaluate the reason for unemployment in patients requiring opioids; whether this relates to the number of nights of PN, pain, side effects of opioids or other disease related factors, or-perhaps most likely-a combination of all of these issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some individuals were unaware they could have flexibility with their infusion schedules, underscoring the importance of having clinician‐patient conversations about goals, priorities, and personal preferences of HPN therapy. When desired by a patient and the clinical situation allows, a reduction in PN frequency should be considered to improve QOL in patients receiving HPN 50 …”
Section: Qolmentioning
confidence: 99%
“…When desired by a patient and the clinical situation allows, a reduction in PN frequency should be considered to improve QOL in patients receiving HPN. 50 The use of patient-reported outcomes (PROs) is a clinically useful approach to monitor progression of disease or response to treatment as well as to improve clinician-patient communication and expand the role of shared or informed decision making. 51 HPN-dependent adults desire a holistic approach to their healthcare with emotional support provided in addition to medical care and nutrition assessment.…”
Section: Qolmentioning
confidence: 99%